2010
DOI: 10.1002/qua.22841
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of XO···ClF and XS···ClF (X = H, CH3, and F) halogen‐bonded complexes

Abstract: Quantum chemical calculations have been performed to study the single-electron halogen bonds in HOÁÁÁClF and HSÁÁÁClF complexes. The calculation methods have a larger effect on the SÁÁÁCl halogen bond than on the OÁÁÁCl one. The interaction strength in HOÁÁÁClF complex is stronger than that in HSÁÁÁClF one, but the presence of methyl group in the halogen acceptor makes the sequence reverse. The methyl group has a greater effect on the SÁÁÁCl halogen bond than on the OÁÁÁCl one. The charge analyses indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The authors suggested the potential of GO crosslinked chitosan nanocomposites in the field of biomaterials. [59] Genipin was also used as a crosslinker between GO and chitosan by Li et al [60] This study showed that the presence of GO leads to a more compact arrangement of chitosan matrix due to hydrogen bonding which hindered the water containment and swelling of the nanocomposites. Therefore, by adding GO, the swelling of hydrophilic polymers can be controlled.…”
Section: Go Content/polymermentioning
confidence: 99%
“…The authors suggested the potential of GO crosslinked chitosan nanocomposites in the field of biomaterials. [59] Genipin was also used as a crosslinker between GO and chitosan by Li et al [60] This study showed that the presence of GO leads to a more compact arrangement of chitosan matrix due to hydrogen bonding which hindered the water containment and swelling of the nanocomposites. Therefore, by adding GO, the swelling of hydrophilic polymers can be controlled.…”
Section: Go Content/polymermentioning
confidence: 99%
“…[42] The delay observed in the equilibrium time may be due to the 2D nature and barrier properties of the fG flakes, delaying the diffusion of water through the film. [58,65] The few-layer graphene flakes are intrinsically hydrophobic, only their surface was modified to become hydrophilic, and thus the weight fraction of fG incorporated in the FS film may have little contribution to the overall WU. Also, the establishment of a good interface between CHI/fG may result in lower ability for water uptake.…”
Section: Water Uptakementioning
confidence: 99%
“…Similar results were reported in the literature for CHI composites, where a decrease in weight loss and degradation rate of CHI was observed after the incorporation of GO. [65,69]…”
Section: Degradation Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other computational studies indicate that the halogen‐bonded HO…ClF complex is more strongly bound than the HS…ClF analogue, but the relative binding strength is reversed when the protons are replaced by methyl groups; i. e. H 3 CO…ClF < H 3 CS…ClF . The variation in the relative strength of halogen and hydrogen bonds in H 2 CS…HOX (X=F, Cl, Br) systems was also investigated, with recommendations made for making halogen bonds stronger than hydrogen bonds .…”
Section: Introductionmentioning
confidence: 99%